Goddess Girls : Clotho the Fate - Joan Holub (India Aladdin, 2019)
Get to know Clotho, one of the Three Fates, in this twenty-fifth Goddess Girls adventure! Eleven-year-old Clotho is always linked with her two big sisters. Together, they are all the Three Fates, with abilities to predict events in mortals$1 (Blives. There are a few rules that the all-powerful Zeus has decreed for them, including a strict no-mingling with mortals policy. After Clotho discovers letterscrolls from unhappy mortals who don$1 (Bt love their fates, she wishes there was a way to try and earn their respect. During a secret trip to the Immortal Marketplace$1 (Bwhere there is always a chance to run into mortals, too!$1 (BClotho finds herself in over her head as she gets swept up in a competition to celebrate the opening a new store. A competition where her identity as a fate could be revealed at any moment! If that weren$1 (Bt enough, Clotho must face up to an old mistake she made several years ago that broke one of Zeus$1 (Bs other rules: Never interrupt the telling of a fate. It could mess up a mortal$1 (Bs whole life! Can Clotho manage to untangle the mess she has made while finding a way to bring the mortals and the Fates together?s
Keywords: Myths & Legends -- Myths & Legends